Remembrance of the historian Vicent Llombart - Almenar Palau, Salvador (Iberian Journal of the History of Economic Thought, 2017)
This remembrance shows how the initial training that Vicent Llombart received at the Seminar on the History of Economic Thought at the University of Valencia was crucial, although not the only element, to understanding a prominent academic career with so relevant contributions. His determined purpose, his self-demanding character and his permanent intellectual openness help us to better understand a great historian.